2011
DOI: 10.1088/0957-4484/22/25/254028
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of resistive switching characteristics in ZrO2film by embedding a thin TiOxlayer

Abstract: The stabilization of the resistive switching characteristics is important to resistive random access memory (RRAM) device development. In this paper, an alternative approach for improving resistive switching characteristics in ZrO(2)-based resistive memory devices has been investigated. Compared with the Cu/ZrO(2)/Pt structure device, by embedding a thin TiO(x) layer between the ZrO(2) and the Cu top electrode, the Cu/TiO(x)-ZrO(2)/Pt structure device exhibits much better resistive switching characteristics. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 17 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…6(a)), show that in OFF-state, conduction mechanism responsible for charge transport in the low voltage region is Ohmic (n ¼ 1.1) but is different in the medium and high voltage regions. IeV behavior in the medium voltage region indicates that the injected carrier density is greater than the free carrier density, which is a typical trap modified space charge limited current (SCLC) conduction mechanism in an insulator with shallow traps [18,19]. The traps might be rare earth oxide impurities which give rise to exponential distribution of localized states in the forbidden gap [20].…”
Section: Resultsmentioning
confidence: 99%
“…6(a)), show that in OFF-state, conduction mechanism responsible for charge transport in the low voltage region is Ohmic (n ¼ 1.1) but is different in the medium and high voltage regions. IeV behavior in the medium voltage region indicates that the injected carrier density is greater than the free carrier density, which is a typical trap modified space charge limited current (SCLC) conduction mechanism in an insulator with shallow traps [18,19]. The traps might be rare earth oxide impurities which give rise to exponential distribution of localized states in the forbidden gap [20].…”
Section: Resultsmentioning
confidence: 99%
“…Good data retention with high resistance ratios of 10 Resistive switching random access memory devices have shown promise for developing low power nanoscale nonvolatile memory technology in the future. [1][2][3][4][5] Many previous studies of this topic have reported solid electrolyte-based resistive switching memory devices that use different materials, such as GeSe x , [6][7][8] CuTe/Al 2 O 3 , 13 and GeSe x /TaO x. 14 Resistive switching occurs because of the formation/dissolution of the silver (Ag) or Cu metallic filament under external bias.…”
mentioning
confidence: 99%
“…I-V and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 EPIR results indicate that the oxygen content has a strong influence on the electrical transport properties for NSMO ceramics. For the oxygen-enriched samples, the I-V characteristic is linear and the EPIR effect is not detectable.…”
Section: Resultsmentioning
confidence: 96%
“…In order to understand the essence of EPIR, a large variety of EPIR-materials were investigated, including binary oxides NiO [9][10][11] , ZrO 2 [12][13] and HfO 2 [14][15][16] as well as complex oxides such as Pr 1 -x Ca x MnO 3 [17][18] , BiFeO 3 [19][20][21] , and SrTiO 3 [22][23][24] . In terms of description we can roughly categorize them into two groups of redox and defects.…”
Section: Introductionmentioning
confidence: 99%